Good Countries or Good Projects? Macro and Micro Correlates of World Bank Project Performance - Denizer, Cevdet; Kaufmann, Daniel; Kraay, Aart (Elsevier, 2013)
This paper investigates macro and micro correlates of aid-financed development project outcomes, using data from over 6000 World Bank projects evaluated between 1983 and 2011. Country-level “macro” measures of the quality of policies and institutions are strongly correlated with project outcomes, consistent with the view that country-level performance matters for aid effectiveness. However, a striking feature of the data is that the success of individual development projects varies much more within countries than it does between countries. A large set of project-level “micro” variables, including project size, project length, the effort devoted to project preparation and supervision, and early-warning indicators that flag problematic projects during the implementation stage, accounts for some of this within-country variation in project outcomes. Measures of World Bank project manager quality also matter significantly for the ultimate project outcomes. We discuss the implications of these findings for donor policies aimed at aid effectiveness.